2011
DOI: 10.1161/strokeaha.110.596684
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Ischemic Penumbra

Abstract: Background— In the last 3 decades, and from a therapeutic point of view, the classical concept of ischemic penumbra based on hemodynamic and electrophysiological parameters has loosened up the rigidity of therapeutic windows in acute stroke management. Thirty years later, the ischemic penumbra is an evolved concept that presents more applications. Thus, the ischemic penumbra is a diagnostic target, allowing the extension of therapeutic windows; it is also a biochemical target, in which an intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 27 publications
3
120
0
2
Order By: Relevance
“…50 The term "penumbra" is now generally used to define ischemic but salvageable cerebral tissue that requires immediate reperfusion. 51 MRS findings and gradual attenuation of NAA in the acute stage of ischemic stroke Typical chronological changes visible by MRS during acute ischemic stroke have been identified in several animal studies [52][53][54][55] and subsequently confirmed in human clinical studies. [56][57][58][59] Typically, chronological changes of four MRS visible metabolites can be seen following cerebral ischemia, namely rise of lactate, and attenuations of NAA, creatine and phosphocreatine (Cr), and choline compounds (Cho).…”
Section: Concept Of Experimental Ischemic Strokementioning
confidence: 76%
“…50 The term "penumbra" is now generally used to define ischemic but salvageable cerebral tissue that requires immediate reperfusion. 51 MRS findings and gradual attenuation of NAA in the acute stage of ischemic stroke Typical chronological changes visible by MRS during acute ischemic stroke have been identified in several animal studies [52][53][54][55] and subsequently confirmed in human clinical studies. [56][57][58][59] Typically, chronological changes of four MRS visible metabolites can be seen following cerebral ischemia, namely rise of lactate, and attenuations of NAA, creatine and phosphocreatine (Cr), and choline compounds (Cho).…”
Section: Concept Of Experimental Ischemic Strokementioning
confidence: 76%
“…There is little evidence of theranostic approaches being used to target areas located inside the brain parenchyma because of the difficulties faced by systemically administered substances in crossing the blood-brain barrier. 23 The multitasking nature of theranostic agents involves construction of complex nanostructures, which affect the capacity of more basic structures, ie, the drug carriers on which they are based, to cross the blood-brain barrier.…”
Section: "Vici": Theranostic Molecules To Treat Diseasementioning
confidence: 99%
“…However, our research group and others have demonstrated that encapsulation of therapeutic agents in targeted theranostic molecules (for example, heat shock protein [HSP]72-targeted liposomes) 23 results in increased efficacy in the treatment of neurological disorders such as stroke ( Figure 6). The top row of Figure 6 shows a series of T1-weighted magnetic resonance images (at 9.4 Tesla) of the brains of three rats that were subjected to an experimental model of ischemia, 19 with superimposed colored maps of changes in longitudinal relaxivity (R1) 24 hours after intravenous injection of a therapeutic agent, cytidine diphosphate-choline (citicoline), in its free state (left), encapsulated in gadolinium-doped liposomes (center, composition described elsewhere by Ramos-Cabrer et al), 19 or encapsulated in the same liposomes with anti-HSP72 antibodies attached to its surface to vectorize the liposomes to the peri-infarct region (right).…”
Section: "Vici": Theranostic Molecules To Treat Diseasementioning
confidence: 99%
See 2 more Smart Citations